Learning through E – Learning (Journal of the College of Basic Education, 2023)
This paper deals with items of E-Learning construction, where the progress in the field of information technology has enabled persons to have a new educational delivery behaviours and methods such as distance learning and E-Learning.There are many universities and collages were entered this new world of E-Learning as a major way for it to use in teach procedures. For this reason the need for pedagogical and technical knowledge to teach using the internet has emerged, and this knowledge field is slowly becoming a core competence for many teachers.The paper sheds some lights on the importance of E-Learning to societies, universities, organizations and individuals. Also, discusses some of the important distance learning methods that are being used by educators, trainers and lectures.For the above mentioned reasons, as an application within this context, we turn to design a web site which handles the provision of the departments’ articles for all the stages in Engineering College with providing the professors and college students the abilities to share their ideas and opinions for developing this education